Gender transformative socio-technical innovation bundles innovation profile for Kenya - Nchanji, Eileen; Lutomia, Cosmas Kweyu; Ketema, Dessalegn; Nicoletta, Buono (2025)
der Transformative Socio-technical Innovation Bundles (STIBs) are co designed combinations of social, technical, and technological innovations that aim to improve climate resilience and empower men, women, youth, and marginalized groups in diverse production systems in Africa and Asia. STIBs are operationalized through learning labs – which can be physical and virtual spaces for multi-stakeholder engagement in innovation processes.